Nanobiointerfaces: Human Platelet Membrane Functionalized Microchips with Plasmonic Codes for Cancer Detection (Adv. Funct. Mater. 30/2019). (23rd July 2019) - Kumar, Sumit; Han, Jae‐A; Michael, Issac J.; Ki, Dongyeob; Sunkara, Vijaya; Park, Juhee; Gautam, Shreedhar; Ha, Hong Koo; Zhang, Liangfang; Cho, Yoon‐Kyoung
Abstract : In article number1902669, Yoon‐Kyoung Cho and co‐workers describe a microfluidic chip equipped with a platelet membrane‐cloaked surface, the "PLT‐Chip, " which takes advantage of the strong and specific interaction between platelets and cancer‐derived extracellular vesicles. The PLT‐Chip accurately detects cancer using ultra‐small volumes (1 µL) of patient's plasma samples, with high sensitivity.